The Lisbon Agreement and the Importance of Protecting Appellations of Origin - Merebashvili, Tornike (European Scientific Journal, ESJ, 2026)
This article examines the Lisbon Agreement for the Protection of Appellations of Origin and their International Registration as a distinct international legal framework within intellectual property law. Employing a doctrinal and comparative legal methodology, the study analyzes the normative structure of the Lisbon system, its registration mechanism, the principle of perpetual protection, and the legal grounds for termination of international registration. Particular attention is paid to the interaction between the Lisbon Agreement and other international legal regimes governing geographical indications, including trademark-based protection models and the TRIPS framework. The article argues that, despite its limited membership, the Lisbon Agreement constitutes an autonomous and high-threshold protection regime rather than a merely supplementary instrument to trademark systems. Its relatively restricted global adoption is explained not by normative weakness, but by its strict conceptual requirements and complex coexistence with dominant intellectual property frameworks. The study concludes that the Lisbon system remains especially valuable for states seeking strong and durable protection of appellations of origin closely linked to territorial identity, traditional knowledge, and cultural heritage.